JKLMR conjecture and Batyrev construction. (22nd March 2019) - Aleshkin, Konstantin; Belavin, Alexander; Litvinov, Alexey
Abstract: We study a mirror interpretation of the relation between the exact partition functions of gauged linear sigma-models (GLSM) on S 2 and Kähler potentials on the moduli spaces of the CY manifolds proposed by Jockers et al . We use the Batyrev mirror construction for establishing the explicit relation between GLSM and the corresponding mirror family of the Calabi–Yau manifolds, defined as hypersurfaces in weighted projective spaces. We demonstrate how to do this by the explicit calculation in the case of the quintic threefold and its mirror.